Dialogue between past and future mathematical identities - Lutovac, Sonja; Kaasila, Raimo (NOMAD Nordic Studies in Mathematics Education, 2012)
Pre-service teachers’ school-time experiences have been addressed much in mathematics education research. These experiences have been shown to have a central meaning for pre-service teachers’ views of mathematics and their present mathematical identities. However, the identity is not only bound to the past and present, but it also extends to the future. Further, pre-service teachers’ anticipations of the future have been overlooked in the research on identity in a mathematics education context. We focus here on the mathematical identity work of two pre-service teachers and its dialogue between the past and the future. We compare the cases of one Finnish and one Slovenian pre-service teacher, who reported having had negative experiences with mathematics during their school years. Based on the results, two different types of mathematical identity work were identified; resulting from the different facilitators used in mathematics education courses.